Economic Acceleration after the COVID-19 Pandemic through Improving the Quality of Human Resources in Rural Communities: A Case Study of Bawuran Tourism Village, Indonesia - Wolor, Christian Wiradendi; Wibawa, Eka Ary; Rababah, Mahmoud Ali; Eranza, Datu Razali Datu (Southern African Journal of Social Work and Social Development, 2023)
Tourist villages which are the driving force of the economy in Indonesia, especially in the rural communities, faced a very difficult situation during the COVID-19 pandemic. However, after the COVID-19 pandemic had reached its final stages, the village community tried to raise the attractiveness of its tourist villages to increase tourism. In this study, we aimed to understand and explore the ways in which the tourism village community of Bawuran sought to increase village economic growth during the pandemic transition to normal life with regard to human resource aspects. The unit of analysis in this study was the tourism village community of Bawuran in Yogyakarta which was identified as one of the top 10 national tourism villages in the Republic of Indonesia to become a world-class tourist village. In this research, we used a qualitative approach with a case-study method, both in data collection and analysis. Observations and semi-structured interviews were used to obtain information. The findings of the study indicated that the indigenous people of the tourist village of Bawuran have a strong will to change and are adaptive to social and technological changes because of receiving extensive training during the COVID-19 pandemic. The results of the training and willingness to change are realised by utilising social media in marketing tourist villages, building attractive spots that pamper tourists, and offering local products in the form of furniture and traditional food through e-commerce.